Effectiveness of Using Virtual Accounting Laboratory on Student Learning Outcomes - Moh. Danang Bahtiar; Luqman Hakim; Eko Wahjudi; Amirul Arif (Economics Education Department Universitas Negeri Semarang, 2024)
The research that has developed so far, the use of virtual laboratories in learning is only widely used for exact science groups such as mathematics, physics or chemistry, while in non-exact science groups it has not been widely done. Therefore, the purpose of this study is to determine the effectiveness of the use of virtual accounting laboratories on student learning outcomes in taxation courses which are non-exact science groups. This type of research is Quasi Experimental research using Nonequivalent Control Group Design. The results of the study showed that the post-test scores in classes that used virtual accounting laboratories increased higher when compared to classes that did not use virtual accounting laboratories. The contribution that is an important finding in this study is the use of virtual accounting laboratories for taxation courses which are non-exact science fields has been proven to be able to improve student learning outcomes.